Kompetensi Auditor dan Audit Internal pada Laporan Keuangan Kabupaten Serdang Berdagai - Ritonga, Achmad Chairul Azhari; Nasution, Nina Andriany; Heriyati Chrisna (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aimed to determine how auditors' ability and the implementation of internal audits affect the quality of Serdang Bedagai Regency Local Government Financial Statements. The data collection method applied is to provide questionnaires or questionnaires to Officers and Auditors of the Inspectorate of Serdang Bedagai Regency. This study uses an associative/quantitative approach and the IBM SPSS Ver.27.0 data analysis tool. This study analyzes civil servants who work at the Inspectorate of Serdang Bedagai Regency. This study uses a saturated sample or census to collect 30 Inspectorate civil servants. This study uses multiple regression analysis to analyze the data. The results showed that the implementation of internal audit and auditor competence simultaneously improved and significantly improved the quality of the financial statements of the Regional Government of Serdang Bedagai